Recent CFD study of fouling in reverse osmosis membrane systems - Tan, Jia Xin; Abdul Latif, Ahmad; Li, Mengheng; Shahabuddin, M.; Liang, Y. Y. (Elsevier Ltd, 2025)
With freshwater resources becoming increasingly limited, efficient and sustainable water treatment technologies are essential to ensure a reliable supply of clean water. Membrane-based separation systems, particularly reverse osmosis (RO), have become a cornerstone of modern desalination and wastewater treatment due to their effectiveness in removing salts and contaminants. However, issues such as concentration polarization (CP) and membrane fouling continue to hinder system efficiency and longevity. Computational Fluid Dynamics (CFD) has emerged as a powerful tool for addressing these challenges by offering detailed insights into fluid flow, solute transport, and fouling behavior. This phenomenon is often difficult to investigate experimentally. This chapter explores the application of CFD in RO membrane processes, focusing on its role in analyzing mass transfer, understanding fouling mechanisms, and evaluating the effects of operating conditions and membrane surface modifications on overall system performance.